Preparo, caracterização e uso da perovskita mesoporosa LaMnO3 como catalisador na produção sustentável de imina em reator de fluxo contínuo - Himad Ahmed Alcamand (2022)
Perovskite-type oxides are considered promising materials to substitute noble metal catalysts, due to their low cost, thermal and chemical stability, and easy adjustment of properties. The perovskite LaMnO3 has shown excellent catalytic activity due to the coexistence of the Mn3+/Mn4+ pair. However, these oxides have limited industrial applications due to the reduced specific surface area and low pore volume caused by the synthesis methods that limit the exposure of the active sites and reduce the catalytic performance. We used the nanocasting method to prepare and characterize mesoporous LaMnO3 perovskites with high specific surface area, larger pore volumes, and smaller particle sizes. For this, we synthesized and used as templates two types of silica with different ordered pore structures, KIT-6 (3D-cubic) and SBA-15 (2D-hexagonal). Results revealed that the perovskites have LaMnO3.15 crystal structure and R-3c space group. However, the resulting materials are not accurate replicas of the templates, but high values were obtained for specific surface areas, larger pore volumes, smaller particle and crystallite sizes compared to the perovskite obtained by the citrate method, which were, respectively: (i) 87 m2.g-1, 0.78 cm3.g-1, 8.3 nm and 8.0 nm for LM-S, (ii) 95 m2.g-1, 0.80 cm3.g-1, 13.5 nm and 11.7 nm for LM-K and (iii) 11 m2.g-1, 0.10 cm3.g-1, 89.7 nm and 58.6 nm for LM-S. XPS analyses revealed that the surfaces of the mesoporous oxides have high relative contents of the Mn3+/Mn4+ pair and the highly oxidizing O22-/O- species compared to that prepared by the citrate method. The catalytic performance was evaluated by oxidative coupling of benzyl alcohol to aniline for imine formation in continuous flow system. The synergistic effect between Mn3+/Mn4+ pair, O22-/O-, reaction temperature and O2 flow rate, influence the catalytic performance which exhibited the following order for stable imine production: LM-S (98 %) > LM-K (85 %)> LM-C (16 %). The catalysts were recovered, recycled and reused in five catalytic cycles, exhibiting the following order for catalytic performance: LM-S (96 %) > LM-K (80 %) > LM-C (10 %), maintaining the crystalline structure.